Estudo do efeito do processo de shot peening na taxa de propagação de trinca por fadiga na liga aeronáutica 2024 - T3 - Costa, Douglas Henrique da Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This work focuses to evaluate the effect of the shot peening process in the propagation rate of a fatigue crack already existing. The shot peening is a cold working process, which consists of repetitive blasting with steel shot, ceramic or glass, the surface of a workpiece, producing hardening and inducing compressive residual stresses on the treated surfaces. Because of this, shot peening has proved a very efficient method for hindering the initiation and propagation of a fatigue crack from the surface of the material, improving its fatigue strength. However, studies of its effect on an already existing crack are little known. Specimens of type CT to the aeronautics aluminum alloy 2024 - T3, were initially cracked by fatigue and then subjected to shot peening process on both sides. After treatment, the tests were resumed under the same conditions. Tests were carried out with constant amplitude in two thicknesses of specimens and two load ratios, R, to analyze possible effects of stress state on the crack tip results. Two shot peening intensities were used for each R value or thicknesses analyzed, and were also studied two application regions of shot peening process (behind and around the crack tip) in two sizes of cracks. Comparative curves of the fatigue crack propagation rate, showing the influence of each of the parameters described are shown, and their differences discussed. The results show that the shot peening process, when performed in a crack size in full stage II propagation, has greater influence when applied behind the crack tip, with lower intensity, in the specimens in plane stress state and lower load ratio. For crack lower (close to the stage I of propagation), the shot peening process applied behind the crack tip induced delay in their propagation rate in all conditions studied. The delay effect on fatigue crack propagation rate ... (Complete abstract click electronic access below)

Este trabalho tem por finalidade avaliar o efeito do processo de shot peening na taxa de propagação de uma trinca por fadiga já existente. O shot peening é um processo de trabalho a frio, que consiste no jateamento repetitivo com microesferas de aço, cerâmica ou vidro, na superfície de uma peça, produzindo encruamento e induzindo tensões residuais compressivas nas superfícies tratadas. Devido a isso, o shot peening tem-se mostrado um método bastante eficiente para dificultar o início e a propagação de uma trinca por fadiga a partir da superfície do material, melhorando a sua resistência à fadiga. Contudo, estudos de seu efeito sobre uma trinca já existente são pouco conhecidos. Corpos de prova do tipo CT, para a liga aeronáutica de alumínio 2024 - T3, foram inicialmente trincados por fadiga e, em seguida, submetidos ao processo de shot peening em ambos os lados. Após o tratamento, os ensaios foram reiniciados nas mesmas condições. Os ensaios foram realizados com amplitude constante em duas espessuras de corpos de prova e duas razões de carga, R, para analisar possíveis efeitos do estado de tensão na ponta da trinca nos resultados. Duas intensidades de shot peening foram utilizadas para cada valor de R ou espessura analisada. Também foram estudadas duas regiões de aplicação do processo de shot peening (atrás e em volta da ponta da trinca) em dois tamanhos de trincas. Curvas comparativas do comportamento da taxa de propagação de trincas por fadiga, mostrando a influência de cada um dos parâmetros descritos, são apresentadas, e suas diferenças, discutidas. Os resultados encontrados mostram que o processo de shot peening, quando realizado em um tamanho de trinca em pleno estágio II de propagação, apresenta maior influência quando aplicado atrás da ponta da trinca, com menor intensidade, em corpos de prova em estado ... (Resumo Completo, clicar acesso eletrônico abaixo)
Study of the effect of the shot peening process on the rate of fatigue crack propagation in aircraft alloy 2024 - T3
Keywords: Ligas de aluminio; Tensões residuais; Fadiga; Ligas de aluminio - Tratamento termico; Mecânica da fratura; Aluminum alloys